To solve the system of equations using substitution, follow these steps, putting them in the correct order:
-
Choose one of the equations to solve for one variable. For instance, you can solve the second equation \( x - 2y = 11 \) for \( x \): \[ x = 2y + 11 \]
-
Substitute this expression into the other equation. Now, substitute \( x = 2y + 11 \) into the first equation \( -7x - 2y = -13 \): \[ -7(2y + 11) - 2y = -13 \]
-
Simplify and solve for the remaining variable. Distribute and combine like terms: \[ -14y - 77 - 2y = -13 \ -16y - 77 = -13 \ -16y = 64 \ y = -4 \]
-
Substitute back to find the other variable. Use the value of \( y \) found in step 3 and substitute it back into the equation from step 1 to find \( x \): \[ x = 2(-4) + 11 \ x = -8 + 11 \ x = 3 \]
-
Combine the results into a solution. The solution to the system of equations is: \[ (x, y) = (3, -4) \]
So the ordered steps to solve the system of equations by substitution are:
- Solve one of the equations for one variable.
- Substitute that expression into the other equation.
- Simplify and solve for the remaining variable.
- Substitute back to find the other variable.
- Combine the results into a solution.